2016
DOI: 10.3762/bjoc.12.115
|View full text |Cite
|
Sign up to set email alerts
|

Biradical vs singlet oxygen photogeneration in suprofen–cholesterol systems

Abstract: SummaryCholesterol (Ch) is an important lipidic building block and a target for oxidative degradation, which can be induced via free radicals or singlet oxygen (1O2). Suprofen (SP) is a nonsteroidal anti-inflammatory drug that contains the 2-benzoylthiophene (BZT) chromophore and has a π,π* lowest triplet excited state. In the present work, dyads (S)- and (R)-SP-α-Ch (1 and 2), as well as (S)-SP-β-Ch (3) have been prepared from β- or α-Ch and SP to investigate the possible competition between photogeneration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Chlorpromazine (CPZ) and sodium dodecyl sulfate (SDS) served as the positive phototoxic and negative non-phototoxic controls, respectively. CPZ is a widely used typical antipsychotic drug with well-known phototoxic properties as already reported ( Palumbo et al, 2016 ). In our recent study, GFT has shown a very significant phototoxic potential in HaCaT cells ( Tamarit et al, 2021 ).…”
Section: Methodsmentioning
confidence: 79%
“…Chlorpromazine (CPZ) and sodium dodecyl sulfate (SDS) served as the positive phototoxic and negative non-phototoxic controls, respectively. CPZ is a widely used typical antipsychotic drug with well-known phototoxic properties as already reported ( Palumbo et al, 2016 ). In our recent study, GFT has shown a very significant phototoxic potential in HaCaT cells ( Tamarit et al, 2021 ).…”
Section: Methodsmentioning
confidence: 79%